Redesign Interior Sweet Shop Fahion Store di Kota Salatiga - Yuna Narita (Intra, 2017)
Sweet Shop Fashion Store in Salatiga would be redesigned to attracts the consumers and be able to compete againts the times. With the up to date branding reform concept, will make Sweet Shop Factory outlet into Sweet Shop Fashion Store and Coffee Shop which not only selling clothes, but it’s become tourist attraction which can attract tourusts within the city and outside the city. Brand identity will be reinforced by store designs that use industrial style design and additional facilities specifically aimed the teenagers. Main entrance is design with bricks material black painted and the coffee shop hopefully become a vocal point in Salatiga. With this interior design reformations, Sweet Shop Fashion Store would be a place that never been exist before which facilitated the visitors whose not only shopping but become a place for relaxing for community, tourists and students.